The in Vivo Role of Androgen Receptor SUMOylation as Revealed by Androgen Insensitivity Syndrome and Prostate Cancer Mutations Targeting the Proline/Glycine Residues of Synergy Control Motifs - Mukherjee, Sarmistha (American Society for Biochemistry and Molecular Biology, 2012)
The androgen receptor (AR) mediates the effects of male sexual hormones on development and physiology. Alterations in AR function are central to reproductive disorders, prostate cancer, and Kennedy disease. AR activity is influenced by post-translational modifications, but their role in AR-based diseases is poorly understood. Conjugation by small ubiquitin-like modifier (SUMO) proteins at two synergy control (SC) motifs in AR exerts a promoter context-dependent inhibitory role. SC motifs are composed of a four-amino acid core that is often preceded and/or followed by nearby proline or glycine residues. The function of these flanking residues, however, has not been examined directly. Remarkably, several AR mutations associated with oligospermia and androgen insensitivity syndrome map to Pro-390, the conserved proline downstream of the first SC motif in AR. Similarly, mutations at Gly-524, downstream of the second SC motif, were recovered in recurrent prostate cancer samples. We now provide evidence that these clinically isolated substitutions lead to a partial loss of SC motif function and AR SUMOylation that affects multiple endogenous genes. Consistent with a structural role as terminators of secondary structure elements, substitution of Pro-390 by Gly fully supports both SC motif function and SUMOylation. As predicted from the functional properties of SC motifs, the clinically isolated mutations preferentially enhance transcription driven by genomic regions harboring multiple AR binding sites. The data support the view that alterations in AR SUMOylation play significant roles in AR-based diseases and offer novel SUMO-based therapeutic opportunities.